Custard Slice (Kotorska Pašta): Tracing the Culinary Journey from French Origins to Kotor’s Local Identity - Ferri, Ane (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2025)
This paper is dedicated to the study of custard slice—a cake that represents a significant part of the cultural heritage of the Bay of Kotor, while also carrying a deeply rooted Mediterranean cultural heritage. Starting from the theoretical foundations of Claude Fischler, who asserts that food is an inseparable part of identity, and Massimo Montanari’s starting point that food is culture, I explore the historical background, the making technique, and the cultural importance of this dessert that arrived in Kotor via Italy. The dessert’s unique position within both local and broader Mediterranean cuisine highlights how food reflects the cultural complexities of the region. The gastronomic identity of this area was shaped by recipes of the most diverse origins, through constant contact with different people, who came, left, stayed, and assimilated with the local population. These interactions—be they cultural, economic, or political—created a culinary landscape that is as diverse as the people who influenced it. Considering the long-term presence of this delicacy in the gastronomy of Kotor, the aim of this paper is to document, for the first time, the evolution of kotorska pašta—not cremeschnitte, as it is often mistakenly called—by analysing historical sources, recipes, and narratives of individuals from the local community. This study reveals the ways in which this dessert has evolved, not only as a recipe but also as a symbol of local identity and continuity. By looking at the shifting contexts in which the custard slice has been prepared and consumed, this paper discusses how it reflects the social and cultural changes in the region over the centuries. My intention is to revive the story of this culinary masterpiece, understanding its importance in the local context and beyond. In doing so, I aim to connect the dessert’s rich history with its modern-day variations, highlighting its enduring relevance in Kotor’s culinary traditions. The methodology of this paper includes the study of historical documents, interviews with local residents, and the analysis of recipes that have been passed down from generation to generation. These sources offer unique insights into how the custard slice has maintained its place in the local culinary repertoire, even as it has adapted to changing tastes and influences. The combination of these methods allows me to create a comprehensive representation of the custard slice, from its beginnings to contemporary adaptations. The paper contributes significantly by documenting cultural heritage through the lens of Mediterranean food culture, enriching the global understanding of local culinary traditions. The study of this dessert provides a powerful example of how food is a living element of culture, constantly evolving yet retaining its roots. In exploring the custard slice, we gain deeper insight into the interplay between culture, identity, and the ways in which food continues to shape and be shaped by the communities that sustain it.